TECHNOGENESIS' CHANGES OF GEOLOGICAL ENVIRONMENT AND VIOLATIONS OF NATURAL GEOCHEMICAL BALANCE IN MINING REGIONS ON THE EXAMPLE OF KRYVBASS - Korzhnev, M.; Malakhov, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A technogenesis at iron ore mining in Krivy Rig Вasin run up the scale of natural geological processes. There is an orders' equality of energy of technogenesis with . Because It sharply the environment geochemistry live conditions for biota and mankind this mining region.